Leukoaraiosis severity and outcomes after mechanical thrombectomy with stent-retriever devices in acute ischemic stroke. (24th July 2018) - Guo, Yongtao; Zi, Wenjie; Wan, Yue; Zhang, Shuai; Sun, Bo; Shang, Xianjin; Li, Shun; Bai, Yongjie; Li, Zibao; Zheng, Dequan; Liu, Xinfeng
Abstract : Background and purpose: The aim of the study was to evaluate whether leukoaraiosis severity is associated with outcome in acute stroke patients undergoing mechanical thrombectomy with stent-retriever devices. Methods: In this retrospective multicenter study, we evaluated 251 acute stroke patients (pretreatment National Institutes of Health Stroke Scale score ≥8) treated with stent-retriever devices. Leukoaraiosis severity was graded as 0–2 (absent-to-moderate) versus 3–4 (severe) according to the van Swieten scale. The main clinical outcome was the proportion of good functional outcome, defined as a modified Rankin Scale of 0–2 at 90 days. Results: Significantly fewer patients in the severe LA group than in the absent-to-moderate LA group achieved a good functional outcome (18.4% vs 50.2%, P<0.001). In multivariable analysis, severe leukoaraiosis was a significant negative predictor of good functional outcome at 90 days (OR, 0.27; 95% CI 0.10–0.77; P=0.014). Conclusions: The severity of leukoaraiosis is independently associated with 90-day functional outcome in acute stroke patients undergoing mechanical thrombectomy with stent-retriever devices.